A Chemically Defined Culture for Tooth Reconstitution - Ziwei Zhang; Hong Hu; Zhiheng Xu; Ce Shan; Hanyi Chen; Kun Xie; Kun Wang; Yifu Wang; Qing Zhu; Yike Yin; Haoyang Cai; Yunqiu Zhang; et al. (Advanced Science)
Abstract It is known for decades that dental epithelium and mesenchyme can reconstitute and regenerate a functional tooth. However, the mechanism of tooth reconstitution remains largely unknown due to the lack of an efficient in vitro model. Here, a chemically defined culture system is established that supports tooth reconstitution, further development with normal anatomy, and prompt response to chemical interference in key developmental signaling pathways, termed as toothoids. By using such a system, it is discovered that, during reconstitution, instead of resetting the developmental clock, dental cells reorganized and restarted from the respective developmental stage where they are originally isolated. Moreover, co‐stimulation of Activin A and Hedgehog/Smoothened agonist (SAG) sustained the initial induction of tooth fate from the first branchial arch, which would be otherwise quickly lost in culture. Furthermore, activation of Bone Morphogenetic Protein (BMP) signaling triggered efficient enamel formation in the late‐stage toothoids, without affecting the normal development of ameloblasts. Together, these data highlight the toothoid culture as a powerful tool to dissect the molecular mechanisms of tooth reconstitution and regeneration.